Investigation of the role of electron cyclotron resonance heating and magnetic configuration on the suprathermal ion population in the stellarator TJ-II using a luminescent probe. (8th January 2018) - Martínez, M; Zurro, B; Baciero, A; Jiménez-Rey, D; Tribaldos, V
Abstract: Numerous observation exist of a population of high energetic ions with energies well above the corresponding thermal values in plasmas generated by electron cyclotron resonance (ECR) heating in TJ-II stellarator and in other magnetically confined plasmas devices. In this work we study the impact of ECR heating different conditions (positions and powers) on fast ions escaping from plasmas in the TJ-II stellarator. For this study, an ion luminescent probe operated in counting mode is used to measure the energy distribution of suprathermal ions, in the range from 1 to 30 keV. It is observed that some suprathermal ions characteristics (such as temperature, particle and energy fluxes) are related directly with the gyrotron power and focus position of the heating beam in the plasma. Moreover, it is found that suprathermal ion characteristics vary during a magnetic configuration scan (performed along a single discharge). By investigating the suprathermal ions escaping from plasmas generated using two gyrotrons, one with fixed power and the other modulated (on/off) at low frequency (10 Hz), the de-confinement time of the suprathermal ions can be measured, which is of the order of a few milliseconds (<4 ms). A model that uses a zero-dimensional power balance is used to understand the de-confinement times in terms of the interaction of suprathermal ions and plasma components. This model also can be used to interpret experimental results of energy loss due to suprathermal ions. Finally, observations of increases (peaks) in the population of escaping suprathermal ions, which are well localized at discrete energies, is documented, these peaks being observed in the energy distributions along a discharge.